2007
DOI: 10.2307/4137021
|View full text |Cite
|
Sign up to set email alerts
|

The Causes of Evolutionary Radiations in Archipelagoes: Passerine Birds in the Lesser Antilles

Abstract: TO investigate why some lineages undergo evolutionary radiation, we compare the passerine avifaunas of the Hawaiian and Galapagos archipelagoes, which have supported well-known radiations of birds, with those of the Lesser Antilles, which have not. We focus on four steps required for the buildup of diversity through allopatric speciation and secondary sympatry: genetic divergence in isolation, persistence of island populations, recolonization of source islands, and ecological compatibility in secondary sympatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 37 publications
1
39
0
Order By: Relevance
“…Because local and regional species richness are strongly related, either measure provides an indication of diversifying selection by cooccurring competing or potentially competing species. Although morphology is evolutionarily conservative (SI Appendix, Nested taxonomic analysis of variance), rapid morphological diversification in some island radiations, such as the Hawaiian honeycreepers (59,60), demonstrates that conservatism is not an intrinsic feature of avian morphological evolution (45). Accordingly, I have not applied phylogenetically explicit analyses that take into account evolutionary relationships of species.…”
Section: Methodsmentioning
confidence: 99%
“…Because local and regional species richness are strongly related, either measure provides an indication of diversifying selection by cooccurring competing or potentially competing species. Although morphology is evolutionarily conservative (SI Appendix, Nested taxonomic analysis of variance), rapid morphological diversification in some island radiations, such as the Hawaiian honeycreepers (59,60), demonstrates that conservatism is not an intrinsic feature of avian morphological evolution (45). Accordingly, I have not applied phylogenetically explicit analyses that take into account evolutionary relationships of species.…”
Section: Methodsmentioning
confidence: 99%
“…Many researchers have suggested that speciation might be limited primarily by factors associated with the persistence of incipient species (13)(14)(15). Models of ephemeral speciation propose that it is relatively easy for lineages to form incipient species, but the vast majority of new species do not persist over macroevolutionary timescales (15,19).…”
Section: Groupmentioning
confidence: 99%
“…This has long been recognized by the paleontological community, where "successful" speciation is believed to entail not only the evolution of reproductive isolation but also the persistence of incipient species (13)(14)(15). For example, speciation might be limited primarily by the rate at which lineages form allopatric isolates (6,16) or by the capacity for geographic range expansion (17,18).…”
mentioning
confidence: 99%
“…Suppression of pathogens leading to high population productivity, saturation of niche space, and broad geographic distribution might increase opportunities for population subdivision and species formation. I have argued elsewhere that specialized pathogens might prevent secondary sympatry by sister taxa and reduce diversification within clades (105,106). Suppression of pathogens would reduce this impediment to diversification.…”
Section: )mentioning
confidence: 99%